2021
DOI: 10.1080/03014460.2021.1998620
|View full text |Cite
|
Sign up to set email alerts
|

Infant sex differences in human milk intake and composition from 1- to 3-month post-delivery in a healthy United States cohort

Abstract: IAHB 1998620 -SUPPLEMENTARY TABLES Supplement Table S1. Comparisons a of bioactive human milk components by infant sex b after excluding outlying values for leptin (n=1observation), adiponectin (n=1 observation) and interleukin-6 (n=2 observations observations) 1-month post-delivery 3-months post-delivery Unadjusted GM Ratio (95% CI) Adjusted d GM Ratio (95% CI) Unadjusted GM Ratio (95% CI) Adjusted e GM Ratio (95% CI) Leptin (pg/ml) --c --c 0.90 (0.74, 1.09) 0.88 (0.75, 1.02) Adiponectin (ng/ml) --c --c 0.95 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…It is worth noting that the two previous studies did not directly observe the actual intake of milk but instead estimated it using isotope-labeled water. Another study that measured infant feed consumption found no difference in volume intake between boys and girls at one month and three months of age [ 9 ]. However, when considering volume intake per kilogram of body weight and daily consumption, girls consumed 126 mL/kg/d while boys consumed 114 mL/kg/d.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the two previous studies did not directly observe the actual intake of milk but instead estimated it using isotope-labeled water. Another study that measured infant feed consumption found no difference in volume intake between boys and girls at one month and three months of age [ 9 ]. However, when considering volume intake per kilogram of body weight and daily consumption, girls consumed 126 mL/kg/d while boys consumed 114 mL/kg/d.…”
Section: Discussionmentioning
confidence: 99%
“…There are previous studies investigating BM macronutrient intakes, but they usually estimated BM intake volume via 24-h test weighing (i.e. weighing infants before and after every feed for a 24-h period) ( 44 , 45 ) during EBF period or using the values reported from the literature ( 46 ) . In this study, 2 H-labelled water was perceived to provide more precise BM intake volume estimates compared with the other methods.…”
Section: Discussionmentioning
confidence: 99%
“…Evolutionary approaches examining how parental investment may interact and influence human milk composition (e.g., Fujita et al, 2019;Powe et al, 2010) have typically centered on whether there are associations between a mother's milk composition and the sex of her infant (e.g., do male infants receive milk that has higher energy density than female infants?). A subset of these papers has directly or indirectly examined the Trivers-Willard hypothesis or the interaction effects between maternal condition and infant sex on milk composition (Eckart et al, 2021;Fujita et al, 2012Fujita et al, , 2019Powe et al, 2010;Quinn, 2013). Trivers-Willard posits that mothers attain greater reproductive success through investing in offspring that are most likely to obtain greater fitness (Trivers & Willard, 1973).…”
Section: Evolutionary Approaches To Human Parental Investment and Hum...mentioning
confidence: 99%